Human Resource Management / Seventh Edition - Jackson H. John; Mathis L. Robert (West Publishing Corporation, 1994)
Preface, Perspectives on Human Resource Management, Nature of Human Resource Management, Human Resource Management: Diversity and Global Issues, Strategic Human Resource Planning, Human Resource Issues in Productivity and Quality, Equal Employment Opportunity, Equal Employment, Impementing Equal Employment, Analyzing and Staffing Jobs, Job Analysis, Recruiting Human Resources, Selecting Human Resources, Training and Developing Human Resources, Orientation and Training, Human Resource Development and Careers, Appraisal of Human Resources, Compensating Human Resources, Compensation Administration, Incentives and Executive Compensation, Employee Benefits, Employee and Labor Relations, Health and Safety, Employee Rights and Discipline, Union-Management Relations, Collective Bargaining and Grievance Management, Human Resource Assessment Systems, Appendices, Glossary, Name and Subject Index.
Preface, Perspectives on Human Resource Management, Nature of Human Resource Management, Human Resource Management: Diversity and Global Issues, Strategic Human Resource Planning, Human Resource Issues in Productivity and Quality, Equal Employment Opportunity, Equal Employment, Impementing Equal Employment, Analyzing and Staffing Jobs, Job Analysis, Recruiting Human Resources, Selecting Human Resources, Training and Developing Human Resources, Orientation and Training, Human Resource Development and Careers, Appraisal of Human Resources, Compensating Human Resources, Compensation Administration, Incentives and Executive Compensation, Employee Benefits, Employee and Labor Relations, Health and Safety, Employee Rights and Discipline, Union-Management Relations, Collective Bargaining and Grievance Management, Human Resource Assessment Systems, Appendices, Glossary, Name and Subject Index.